Hepatoprotective and antioxidant polyphenols from a standardized methanolic extract of the leaves of Liquidambar styraciflua L. - Hanaa H. Eid; Rola M. Labib; Nagy S. Abdel Hamid; Manal A. Hamed; Samir A. Ross (Faculty of Pharmacy, Cairo University, 2015)
The methanolic extract of the leaves of Liquidambar styraciflua L. (Altingiaceae) (LSE) was evaluated for hepatoprotective and antioxidant activities in carbon tetrachloride liver-damaged rats. Hepatotoxicity was induced via intraperitoneal injection of CCl4 1:9 in olive oil, at a dose of 0.5 ml/kg b.wt. The animals received the extract, orally, at two dose levels (250 and 500 mg/kg b.wt.) The administration regimen was twice a week, for six consecutive weeks. LSE exhibited a significant dose-dependent protective effect by lowering the serum levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), malondialdehyde (MDA) and ameliorating the level of serum protein. In addition, LSE showed antioxidant activity through improving the levels of blood glutathione (GSH), vitamin C, vitamin E and hepatic total protein contents. The LSE revealed activity approached that of silymarin, a known hepatoprotective agent. These biochemical observations were supported by examination of the histopathological features of the liver. Chromatographic fractionation of LSE afforded seven phenolic compounds. These were identified on the basis of chromatographic, chemical and spectroscopic analyses as: gallic acid (1), isorugosin B (2), casuarictin (3), quercetin-3-O-β-d-4C1-glucopyranoside (4), myricetin-3-O-α-l-1C4-rhamnopyranoside (myricetrin) (5), quercetin (6) and myricetin (7). The isolated phenolics probably account for the antioxidant and hepatoprotective effects exhibited by the parent extract. Furthermore, a validated RP-HPLC method was devised for standardization of LSE, in view to fulfill the requirements of efficient research methodology for evaluation of bioactive herbal drugs. The above findings suggested that LSE could be considered as a standardized herbal product with antifibrotic, hepatoprotective and antioxidant potential.